2022
DOI: 10.1016/j.omtn.2021.12.017
|View full text |Cite
|
Sign up to set email alerts
|

DRAM1 increases the secretion of PKM2-enriched EVs from hepatocytes to promote macrophage activation and disease progression in ALD

Abstract: DNA damage-regulated autophagy modulator 1 (DRAM1) could play important roles in inflammation and hepatic apoptosis, while its roles in alcohol-related liver disease (ALD), which is characterized by hepatic inflammation and apoptosis, are still unclear. In this study, we explored the expression, role, and mechanism of DRAM1 in ALD. Firstly, our results showed that DRAM1 was significantly increased in liver tissues of mice at the early stage of alcohol treatment. In addition, DRAM1 knockout reduced, and liver-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In addition, we found that DRAM1 was prominently expressed in regions at or near the plasma membrane of RAW264.7 macrophages. Plasma membrane expression of DRAM1 has also been observed in hepatocytes and two other members of the DRAM family, DRAM3 and DRAM5, also display plasma membrane expression [24,26,38]. Additionally, we observed the formation of circular DRAM1-positive structures near the plasma membrane that might be the result of endocytosis, for example of cell debris, and therefore derived from the plasma membrane in regions where DRAM1 is highly concentrated.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, we found that DRAM1 was prominently expressed in regions at or near the plasma membrane of RAW264.7 macrophages. Plasma membrane expression of DRAM1 has also been observed in hepatocytes and two other members of the DRAM family, DRAM3 and DRAM5, also display plasma membrane expression [24,26,38]. Additionally, we observed the formation of circular DRAM1-positive structures near the plasma membrane that might be the result of endocytosis, for example of cell debris, and therefore derived from the plasma membrane in regions where DRAM1 is highly concentrated.…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, we observed the formation of circular DRAM1-positive structures near the plasma membrane that might be the result of endocytosis, for example of cell debris, and therefore derived from the plasma membrane in regions where DRAM1 is highly concentrated. This expression pattern of DRAM1 is particularly interesting in the light of a recent study reporting a role for DRAM1 in extracellular vesicles formation [38]. Since exosomes are crucial for communication between immune cells, this might point to an unexplored role for DRAM1 in the intercellular propagating of signals during infection.…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, we observed the formation of circular DRAM1-positive structures near the plasma membrane that might be the result of endocytosis, for example, of cell debris, and that, therefore, derived from the plasma membrane in regions where DRAM1 is highly concentrated. This expression pattern of DRAM1 is particularly interesting in the light of a recent study reporting a role for DRAM1 in extracellular vesicle formation [ 44 ]. Since exosomes are crucial for communication between immune cells, this might point to an unexplored role for DRAM1 in the intercellular propagating of signals during infection.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, we found that DRAM1 was prominently expressed in regions at or near the plasma membrane of RAW264.7 macrophages. Plasma membrane expression of DRAM1 has also been observed in hepatocytes, and two other members of the DRAM family, DRAM3 and DRAM5, also display plasma membrane expression [ 27 , 29 , 44 ]. Additionally, we observed the formation of circular DRAM1-positive structures near the plasma membrane that might be the result of endocytosis, for example, of cell debris, and that, therefore, derived from the plasma membrane in regions where DRAM1 is highly concentrated.…”
Section: Discussionmentioning
confidence: 99%
“…Third, previous works, including ours, have shown that apoptotic or hypoxic stress induce the translocation of PKM2 to the nucleus and cell surface in several cancers 25 , 65 , 66 . Fourth, ethanol or hypoxia increases the expression of PKM2, which is frequently observed in exosomes and ectosomes secreted from the cancer cell surface 67 , 68 . Moreover, our current and previous studies both indicate that hypoxia induces increased PKM2 expression in HCC 25 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%